Precambrian lithospheric evolution of the Fennoscandian Shield - N. Sharov; L. P. Sviridenko (Геофизический журнал, 2017)
Generalized reconstructions have been made on the basis of integrated DSS and CDP data and seismological evidence of local and remote earthquakes obtained for the Fennoscandian Shield over the last forty years. They have provided quantitative information on the horizontal and vertical heterogeneities of the lithosphere. Three-dimensional seismogeological models for some parts of the Fennoscandian Shield have been constructed for the first time. They show that the crystalline crust attains a blocky-hierarchical structure and that no persistent seismic boundaries have been found within the entire shield. In the upper part of the crust, both waveguides and high-velocity zones, which correlate with geological bodies, occur locally. The structural plans of velocity isolines in various deep sections have been found to be inconsistent. It has been proved that major geological provinces differ in crustal thickness, while Early Proterozoic volcanogenic belts display elevated velocities and crustal thickness. Anomalously high velocity layers in the upper mantle of the Fennoscandian Shield have been identified. The structure of the upper portion of the lithosphere was found to be geologically and geophysically related to the geological units of the Palaeoproterozoic East Scandinavian basic large igneous province.